S51 Klotho is associated with skeletal muscle dysfunction and oxidative stress in COPD. (14th November 2013) - Patel, MS; Donaldson, AV; Natanek, SA; Bruijnzeel, PLB; Hopkinson, NS; Man, W D-C; Kemp, PR; Polkey, MI
Abstract : Introduction: Klotho is a transmembrane protein; klotho null mice develop sarcopenia and emphysema. We have previously found serum soluble klotho levels to be lower in COPD patients (ATS 2013). We hypothesised that klotho protects against muscle dysfunction by reducing oxidative stress which is a known feature of skeletal muscle dysfunction in COPD. Aims: To relate quadriceps klotho levels to protein carbonylation and muscle strength in COPD patients. To determine the effect of smoking cessation on vastus lateralis protein carbonylation and klotho. Methods: In 47 COPD patients (mean FEV1 53 (23)%pred), we measured fat-free mass index (FFMI) and quadriceps strength (as QMVC/BMI). Klotho and protein carbonylation were assessed in vastus lateralis protein extracts. 7 current smokers (3 with COPD) had measurements before and after successful smoking cessation. Differences were assessed by Mann-Whitney and relationships by Spearman'. Response to smoking cessation was determined by paired Wilcoxon. Results: Vastus lateralis protein carbonyls were related to klotho levels (r = 0.34, p = 0.02). Patients with a low FFMI (n = 12) had increased klotho levels compared to those who did not, 14.0 (8.5, 30.0) v 9.2 (6.5, 13.2) pg/mg; p = 0.04, however, protein carbonyls were not different (p = 0.08). Conversely, patients with muscle weakness defined as a QMVC/BMI below 1.2 (n = 24) had higher protein carbonylation, 0.76 (0.52, 0.99) v 0.51 (0.40, 0.71) nmol/mg; p = 0.04, but no difference in klotho (see figure 1 ). Patients with both a low FFMI and QMVC/BMI (n = 6) had elevated levels of klotho and protein carbonyls (p = 0.02 and p = 0.03 respectively). In those completing smoking cessation, protein carbonyls, tended to fall, 0.75 (0.64, 1.24) to 0.61 (0.50, 0.71) nmol/mg; p = 0.08, however, klotho levels did not change (p = 0.38). Conclusions: Klotho levels are related to oxidative stress within the quadriceps. Klotho levels are unexpectedly higher in those with reduced FFMI without increased oxidative stress. However, when there is loss of muscle mass and strength, increased klotho levels in muscle are accompanied by increased oxidative stress. Klotho may have a protective role against chronic oxidative stress in the skeletal muscle of patients with a reduced FFMI.